COATING ALLOYS OF CHROMIUM WITH MOLYBDENUM AND TUNGSTEN TO IMPROVE WEAR RESISTANCE OF MACHINE UNITS - Dorohan, T. Ye.; Gerasymenko, D. V. (Science and Transport Progress, 2007)
The article studies phase composition of etlectrically settled wear-proof coatings of the chromium alloys with tungsten and molybdenum. The basic finding may be applied in machine-building for increasing the service life of units, working under large specific loadings, and for the restoration of the worn-out parts.